Strengthening and Repair of Parabolic RC Beam Using Carbon Fiber – Reinforced Polymer Under Repeated Load - Sulaivani, Bayar Jafar; Amin, Tara Najmadin Hama (Sulaimani Journal for Engineering Sciences, 2016)
The aim of this study is to evaluate the effect of (CFRP) on parabolic beams under repeated load. In this study nine parabolic reinforced concrete beams were prepared having (150 x 200mm) dimensions , two unstrengthened as control beams and others were divided in to two groups (A and B) . Group (A) consisted of four beams wrapped with (CFRP) in different ways , group (B) included three damaged beams loaded to about (55%) of the maximum load of control beams and then repaired by (CFRP) . All beams tested under repeated load by (10kN) in one cycle. The test results showed the (CFRP) increased the strength of the parabolic RC beams based on the shape and type of the strengthening.
Keywords: Parabolic RC beam; CFRP; Repeated load